Epidemiological and histopathological profile of cutaneous melanoma at a center in northeastern Brazil from 2000 to 2010 - Camila Maria Arruda Vilanova; Rafael Bandeira Lages; Sahâmia Martins Ribeiro; Isabella Parente Almeida; Lina Gomes dos Santos; Sabas Carlos Vieira (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: While representing only 3-4% of malignant skin tumors, cutaneous melanoma is the most aggressive and lethal. Statistical knowledge about the biological behavior of this tumor is essential for guiding daily outpatient practice and aiding public health policies.OBJECTIVES: To analyze the profile of patients with cutaneous melanoma attending a pathology department in Teresina (state of Piauí) between 2000 and 2010.METHODS: Retrospective study of melanoma patients diagnosed between 2000 and 2010 in the São Marcos Hospital in the city of Teresina. The pathology laboratory reports were studied and all the statistical analyses performed using SPSS 19.0.RESULTS: A total of 25 in situ, 199 invasive and 89 metastatic melanomas of unknown primary site were observed. Histological types found were nodular (52.8%), superficial spreading melanoma (18.6%), acral (10.6%) and lentigo maligna (9.5%). In 144 (73.4%) cases the Breslow thickness was >1 mm. Metastasis was found in 28.6% of invasive melanomas and nodular melanoma, Clark IV/ V, Breslow > 1 mm, mitotic index > 6 and ulcerated lesions were more likely to metastasize.CONCLUSION: Most melanomas presented Breslow> 1mm. The main factors associated with metastasis were nodular type, Clark IV / V, Breslow> 1mm, mitotic index > 6 and ulcerated lesions.